SIMULASI REMOTE CONTROL PADA MESIN PENGUMPUL SAMPAH MENGGUNAKAN ARDUINO NANO BERBASIS MODUL KOMUNIKASI LORA - Vitria, Rikki; Adli, Arif Rafid; Firdaus, Firdaus (Jurnal Ilmiah Poli Rekayasa, 2025)
This research aims to develop a remote control system for waste collection machines using Arduino Nano and LoRa communication modules. The background of this research is the need for an effective remote control system to manage waste collection machines automatically. This system is designed to optimize the machine control process through stable wireless communication. The research process begins with system design, including block diagrams and flowcharts for remote control transmitters and receivers. The transmitter uses an Arduino Nano to read input from the button and send data via the LoRa module. The receiver receives signals from the transmitter, then controls the motor using the L298N motor driver module based on the data received. The research results show that the system can control the motorbike accurately according to the signals received, including forward, backward, right turn and left turn movements. The system is also capable of handling button combinations for more complex motor control. The use of Fritzing and Visual Studio Code in the design and programming process makes system implementation and testing easier. This research provides a practical solution for remotely controlling waste collection machines with LoRa communication.